Mechanism and Molecular Targets of Ejiao Siwu Decoction for Treating Primary Immune Thrombocytopenia Based on High-Performance Liquid Chromatograph, Network Pharmacology, Molecular Docking and Cytokines Validation - Wang, Ming Jing; Sun, Yan; Song, Ying; Ma, Ju Ning; Wang, Zi Qing; Ding, Xiao Qing; Chen, Hai Yan; Zhang, Xue Bin; Song, Min Min; Hu, Xiao Mei (Frontiers in Medicine, 2022)
We explored the mechanisms and molecular targets of Ejiao Siwu Decoction (EJSW) for treating primary immune thrombocytopenia (ITP) using network pharmacology and molecular docking. Active compounds of EJSW were identified by high-performance liquid chromatography-diode array detector (HPLC-DAD) and high-performance liquid chromatography-mass spectrometry (HPLC-MS) and their targets were obtained from HERB and SwissTargetPrediction, and ITP targets were obtained from Comparative Toxicogenomics Database (CTD) and GeneCards. STRING and Cytoscape were used for protein-protein interaction (PPI) network analysis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses by WebGestalt yielded a gene-pathway network, Autodock molecular docking was applied to screen targets and active compounds, and cytokines were detected using a cytometric bead array (CBA) human inflammation kit. We identified 14 compounds and 129 targets, and 1726 ITP targets. RAC-alpha serine/threonine-protein kinase（AKT1）, tumor necrosis factor（TNF）, interleukin-6 (IL6), caspase-3 (CASP3) and tumor suppressor protein (TP53) were core targets (nodes and edges). Functional annotation identified cofactor binding and coenzyme binding, and 20 significantly enriched pathways. Active compounds of EJSW were successfully docked with ITP targets. Tumor necrosis factor alpha (TNF-α) and interleukin-1 beta (IL-1β ) were upregulated in ITP patients, vascular endothelial growth factor A（VEGF-A）and vascular endothelial growth factor D（VEGF-D）were downregulated, and EJSW treatment reversed these trends. EJSW may regulate key ITP targets, and protect vascular integrity through AGE-RAGE signalling, complement and coagulation cascades, and VEGF signalling by downregulating TNF-α, IL-1β and other inflammatory factors.